Eksplorasi Proses Fermentasi Beras Ketan Menjadi Tape Sebagai Sumber Belajar IPA di Sekolah Dasar - Fadiatur Rosidah; Muhammad Suwignyo Prayogo; Tsania Nailal Ilfa; Risa Fitria Agustina (Universitas Palangka Raya, 2025)
This study aims to explore the fermentation process of glutinous rice into tape and its potential as a source of learning Natural Sciences (IPA) in elementary schools. The fermentation process is a real example of chemical changes that can be directly observed by students. Through a contextual approach and simple experiments, students can understand basic concepts such as microorganisms, changes in substances, and factors that influence fermentation. This study uses a qualitative descriptive method with observation, interviews, and documentation studies. The results of the exploration show that the tape fermentation process can be used as an interesting and relevant learning media to improve the understanding of science concepts as a whole and encourage students' active involvement in the learning process.